Digital Collage-As a Pedagogical Tool for Effective Learning of Immunological Concepts - Desai, S. V. (Journal of Engineering Education Transformations, 2018)
Digital collage is an extended version of traditional collage which has gained immense acceptance in the recent days It is a form of graphic art that uses virtual images from various online sources and juxtaposed together to from one assemblage to convey a specific theme. Immunology, as a course is intricately associated and holds scientific rationale for several aspects of daily life. The course provides immense scope for context-building and story-telling exercises for teaching-learning process.The objective of the pedagogical exercise was to attain a comprehensive understanding of the concept by engaging the students in active-learning through story-building and collage-making. The activity was performed for Immunology course of IV semester undergraduate students of Engineering in Biotechnology. Twelve topics, central to the understanding of the course and their applications were selected for the activity and assigned to each student group. The activity comprised three phases: 1). Drafting of technical sketch related to the topic; 2). Story-building to explain the topic&developing a digital-collage to elucidate the same and 3). Oral presentation of the activity by the group members. The contents of the technical script and stories developed were reviewed for the relevance to the topic and feasibility for collage-making. A common template was followed to ensure an uniform pattern of collage layout. The activity was followed by rubrics based assessment and mapping to Graduate attributes, Global competence and Performance Indicators. The activity was instrumental in addressing the graduate attributes related to understanding of domain knowledge, oral and written communications. A formal feedback based on anonymity was collected and the results analyzed. Majority of the respondents opined that the activity was a new experience which helped in deeper understanding of the concept, sensitized their creativity, honed their communication skills and incited a sense of concerted team-work.